2015
DOI: 10.1021/acs.est.5b00217
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft-Based Estimate of Total Methane Emissions from the Barnett Shale Region

Abstract: We present estimates of regional methane (CH4) emissions from oil and natural gas operations in the Barnett Shale, Texas, using airborne atmospheric measurements. Using a mass balance approach on eight different flight days in March and October 2013, the total CH4 emissions for the region are estimated to be 76 ± 13 × 10(3) kg hr(-1) (equivalent to 0.66 ± 0.11 Tg CH4 yr(-1); 95% confidence interval (CI)). We estimate that 60 ± 11 × 10(3) kg CH4 hr(-1) (95% CI) are emitted by natural gas and oil operations, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
258
4

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(270 citation statements)
references
References 33 publications
(76 reference statements)
8
258
4
Order By: Relevance
“…The methodology uses a combination of box-like aircraft flight patterns enclosing each of the main surface mining facilities, comprehensive measurement methods at high time resolution, and the development and application of a computational top-down emission rate retrieval algorithm (TERRA) (25) for deriving facility emission rates from measurements of chemical concentration and meteorology. In contrast to previous aircraft VOC emission studies (26)(27)(28)(29), horizontal and vertical advection and diffusion, chemical reactions, and air mass density changes, all based on measurements, were included in the computation of mass balance of the VOCs from the aircraft measurements, thus reducing the uncertainties in the derived emission rates (25). Another advantage of this methodology is its ability to provide the emission rates of tracers used for the determination of emission rates for many VOCs from discrete measurements, such as canister sampling.…”
Section: Significancementioning
confidence: 77%
“…The methodology uses a combination of box-like aircraft flight patterns enclosing each of the main surface mining facilities, comprehensive measurement methods at high time resolution, and the development and application of a computational top-down emission rate retrieval algorithm (TERRA) (25) for deriving facility emission rates from measurements of chemical concentration and meteorology. In contrast to previous aircraft VOC emission studies (26)(27)(28)(29), horizontal and vertical advection and diffusion, chemical reactions, and air mass density changes, all based on measurements, were included in the computation of mass balance of the VOCs from the aircraft measurements, thus reducing the uncertainties in the derived emission rates (25). Another advantage of this methodology is its ability to provide the emission rates of tracers used for the determination of emission rates for many VOCs from discrete measurements, such as canister sampling.…”
Section: Significancementioning
confidence: 77%
“…Despite these omissions, the EPA estimates that 85-90 % of US GHG emissions are covered under the GHGRP. Other recent studies, however, argue that the GHGRP is less complete than estimated by the EPA for two reasons (e.g., Kort et al, 2014;Karion et al, 2015;Lan et al, 2015;Lavoie et al, 2015;Lyon et al, 2015;Mitchell et al, 2015;Subramanian et al, 2015;Zimmerle et al, 2015). First, the emissions that are excluded from the GHGRP are sometimes larger than estimated by the EPA, and second, the EFs used in the GHGRP are smaller than actual emissions from some source sectors like oil and natural gas.…”
Section: Recent Bottom-up Effortsmentioning
confidence: 98%
“…Furthermore, Brantley et al (2014) explain that these leaks do not correlate with production and can vary greatly in time. Different oil and gas drilling basins also have different overall leakage rates -from 0.3 % in Pennsylvania's Marcellus Shale region to 8.9 % in Utah's Uintah Basin (e.g., Karion et al, 2013Karion et al, , 2015Pétron et al, 2014;Peischl et al, 2015). These factors make it challenging to create consistent, generalizable EFs that can translate activity data into emissions.…”
Section: Recent Direct Measurements That Support Bottom-up Effortsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent field studies have sought to quantify these uncertainties. For example, Allen et al (2015a) assessed differences between observed and inventoried pneumatic controller activity factors and reported a factor of 2-3 difference between observed numbers of pneumatic controllers per well Aircraft-based measurements upwind and downwind of production regions; methane measured using high-precision, high-time-resolution instruments, absorption spectrometry at precise infrared wavelengths; light alkanes analyzed from discrete air samples Emissions (0.48 ± 0.13 Tg/yr) 6.2-11.7% of natural gas production Bottom-up inventories for cattle and gas seepage were subtracted from total emissions; difference assigned to oil and gas activity based on methane to light-alkane ratios Barnett Shale Karion et al, 2015 Aircraft-based measurements upwind and downwind of production regions; methane measured using high-precision, high-time-resolution instruments, absorption spectrometry at precise infrared wavelengths…”
Section: Comparisons Of Emission Estimates With Measurementsmentioning
confidence: 99%